Data Warehouse Design for Multi Finance Companies - et. al., Murnawan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data is an important asset in an organization which is the basis for managers company to make policies, carry out strategies, or make decisions. Data processing can be done in various places, for example in databases operational, operational applications, or using technology data warehouse. The system data warehouse is connected to heterogeneous data sources and is used by decision makers to analyze the conditions and development of the organization. In this research, the initial stage is to carry out a system analysis database operational, studying the software and hardware used at PT XYZ to get an understanding of the current system requirements. Then data warehouse will be designed and set the ETL (Extract, Transformation, Loading) data needed from the database system that is running to the data warehouse that has been designed. The design of a data warehouse uses the Kimball method which consists of nine stages of the methodology (nine-step methodology). With the design results, it is hoped that it can provide a design data warehouse that can be implemented easily to support activities business analysis multi-finance and answer business questions quickly, flexible, and accurate